TEACHERS’ PERCEPTION ON STUDENTS’ ENGAGEMENT IN BLENDED LEARNING IN EFL READING CLASSROOM - Restiana Olivia Pramadita (English Education and Applied Linguistics Journal (EEAL Journal), 2022)
In this pandemic era, blended learning model applied in school one of them in teaching EFL. Blended learning is a relatively new field that combines traditional teaching approaches with online learning. Other than that, students’ engagement is a key aspect in the improvement of getting to know in classroom. The purpose of this research is to find out students’ engagement in blended learning in EFL reading classroom from the teacher's point of view. This research guided by qualitative research approach with case study design. This research was conducted at one of junior high school in Garut. The participants in this research are three English teachers from that school. The data was collected through face-to-face and online interviews. To analyze the data of this research, researcher used inductive analysis data. The findings of this research based on teachers’ perception from participants are behavioral engagement of students in blended learning in EFL reading classroom have the same position between offline and online learning in classroom. Cognitive engagement of students in blended learning in EFL reading classroom more positive when offline learning than when online learning. Emotional engagement of students in blended learning in EFL reading classroom more positive when offline learning than when online learning. It means that in blended learning, student involvement is more likely to look good or positive during offline learning compared to online learning.